Immutability of Distributed Hash Model on Blockchain Node Storage - Rahardja, Untung; Hidayanto, Achmad Nizar; Lutfiani, Ninda; Febiani, Dyah Ayu; Aini, Qurotul (Universitas Negeri Semarang, 2021)
The blockchain system uses hash functions. Hash is used in the blockchain to mark each block of data. Hash function algorithms map a string that is usually hexadecimal of any size to a sequence of fixed-size bits. This journal will discuss the distributed hash model for immutable blockchain node storageThe methodology used in the preparation of this research is mind mapping and literature review, namely the collection of scientific journals, articles and ebooks. Storage of nodes on the blockchain using a distributed hash model. The distributed hash model only stores a portion of the block data at each node, and the block data is taken as a resource. A hash connects each block with the previous on the blockchain, so the entire blockchain transaction cannot be changed or deleted.Â For further research will expand the research topic regarding storage immutability on the blockchain so that it becomes more complete and detailed.